Islam Negeri Selangor Tahun 2003 Mengenai Pendaftaran Poligami di Mahkamah Rendah Syariah Hulu Langat Selangor (Studi Kasus Mahkamah Rendah Syariah Negeri Selangor, Malaysia) - Muhammad Syukri Albani; Hasbullah Dja'far; Muhammad Syazwan Bin Basri (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
According to Law Number 16 of 2019 amendments to Law Number 1 of 1974 Article 1 concerning Marriage. Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on God Almighty. According to Enakmen 2 of 2003 Part 2 of the Selangor State Islamic Family Law of 2003 concerning the subject of marriage. Marriage is a bond born between a man and a woman in forming a household with the words Ijab and Qabul. Polygamy or marrying more than one wife is not a new problem, it has existed in human life for a long time among various groups of people in various worlds. Arabs were polygamous long before the arrival of Islam, as were other societies in most countries of the world during that time. This form of polygamy was known among the Medes, Babylonians, Abbesians and Persians. In Persia, the principle of polygamy is the basis of the family. The number of wives a man can have depends on his economic capacity. Prophet Muhammad SAW allowed polygamy for his people because he had practiced polygamy. However, the Greeks for the most part had a wife who was not only interchangeable, but also commonly traded between them. The same thing can be found in Rome in Ancient Rome, where the position of women reached its lowest point.